1997
DOI: 10.1103/physreve.56.3290
|View full text |Cite
|
Sign up to set email alerts
|

Effects of container geometry on granular convection

Abstract: In this work we use computer simulations to examine the effects of boundary conditions on convection in vibrated granular systems. A two-dimensional model reproduces experimental results on the form of the convective velocities and the reversal of the convection rolls. We then look in detail at the role of the wall preparation and discuss a possible mechanism to account for the range of observed behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(36 citation statements)
references
References 34 publications
2
34
0
Order By: Relevance
“…Particles closer to the walls show a downward movement whereas the particles in the central part of the container start moving upward but with very slow movements. Such a convection phenomenon is referred as normal convection [7]. By increasing the K v value, faster convection movement of the particles is observed as shown in Fig.…”
Section: Simulation Results In Comparison With Literaturementioning
confidence: 94%
See 1 more Smart Citation
“…Particles closer to the walls show a downward movement whereas the particles in the central part of the container start moving upward but with very slow movements. Such a convection phenomenon is referred as normal convection [7]. By increasing the K v value, faster convection movement of the particles is observed as shown in Fig.…”
Section: Simulation Results In Comparison With Literaturementioning
confidence: 94%
“…By tilting the side walls of the container outwards, the direction of the convection cells can be reversed [3]. Grossman [7] studied the transition between normal and reversal convection rolls. He scrutinized the force experienced by the particles closer to the walls by preparing walls of different roughness.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, she identified that the physical mechanism at work was the densitydependent wall friction for both normal and reversed rolls. The direction of the roll depended on when the peak in density occurred in relation to the relative velocity of the side walls, and was influenced in turn by the angle of inclination of the side walls and its roughness [67]. In the vibro-fluidized regime discussed in section 3.1, there is very little density variation with the drive cycle, and therefore convection should be absent.…”
Section: Boundary and Interstitial Air-driven Convectionmentioning
confidence: 99%
“…The effects of the container boundary were examined in detail using computer simulations by Grossman [67]. The numerical and the experimental data for the mean velocity as a function of distance from the centre could be fitted with a parabolic function for low container diameters and by a hyperbolic cosine function for wider containers [65,67].…”
Section: Boundary and Interstitial Air-driven Convectionmentioning
confidence: 99%
“…However, sorting can also be driven by a difference in particle densities, and this is known as the reverse Brazil-nut effect [2,3]. Various studies have shown that segregation depends not only on the particle properties such as size and density, but also on the container's geometry, and friction between the particles and the container's walls [4,5]. Segregation need not always occur along the shaking direction; indeed there are instances where the mixture separates transverse to the vibration direction [6,7].…”
Section: Introductionmentioning
confidence: 99%